Elements of Marketing and Management - (BUCUROIU), Ionela Luminita CANUTA; IOANA, Adrian; SEMENESCU, Augustin; Pollifroni, Massimo (New Advances in Business, Management and Economics Vol. 7, 2025)
Marketing is a whole system of economic activities related to pricing, promotion, and distribution of products and services designed to meet the requirements of actual and potential consumers. This study provides several complementary definitions of marketing. It also presents several key points related to marketing policy: defining the position that the company will occupy on the market for competition, fixing the image with what will approach the market, achieving a balance between turnover rates, profit and expenses as a condition for the survival of the company. This study proposed a concept of marketing management. This concept takes into consideration, on the one hand, the correlations between company's position in the market definition and, on the other hand, the image received by customers. The goal of this concept of marketing management is to ensure an effective balance between the turnover rate of profit and the expenses of the company. Marketing encompasses design, attitude, and action, with a stated focus on customer satisfaction. However, profit often remains the primary goal of organisations. Efficient marketing should be from the beginning to the end of each production cycle and the sales capacity of the undertaking.